2018
DOI: 10.1016/j.jtcme.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two different herbal toothpaste formulations in the reduction of plaque and gingival inflammation in patients with established gingivitis – A randomized controlled trial

Abstract: BackgroundPlant based toothpastes have received great attention in reducing gingival inflammation. Studies show contrasting results regarding the effectiveness of these toothpastes. In the present study, the effectiveness of two herbal tooth paste formulations in the reduction of plaque and gingival inflammation was assessed. Nicotine content in the toothpastes was assessed using GCMS.Material and methods50 patients with established gingivitis were included in the study. The subjects were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 14 publications
3
31
0
4
Order By: Relevance
“…Only in one study did four participants discontinue the study because of disliking the dentifrice taste . In another study, the participants complained of an unpleasant taste in the initial period when using a BS‐DF . Ulcerations were reported in one study, but they appeared unrelated to the trial and eventually .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Only in one study did four participants discontinue the study because of disliking the dentifrice taste . In another study, the participants complained of an unpleasant taste in the initial period when using a BS‐DF . Ulcerations were reported in one study, but they appeared unrelated to the trial and eventually .…”
Section: Resultsmentioning
confidence: 95%
“…The search of the MEDLINE‐PubMed and Cochrane‐CENTRAL databases resulted in 184 unique papers. Manual searching of the reference lists of the final selected papers provided two additional relevant papers, Al‐Kholani et al, listed by Hosadurga et al and Akwagyiram et al, listed by Bosma et al Altogether, 21 eligible publications were found . Among these, Putt et al and Mason et al provided five and two sub‐studies, respectively, within their main publications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical treatments such as UV rays also impair the effective uptake of inactivated viruses by antigen-presenting cells through interfere with viral lipid membrane activity. Thereby, the efficacy of inactivated vaccines may be reduced by these structural alterations [2,11,22]. In contrast, the virucidal effect of gamma irradiation is mainly related to the viral nucleic acid damage [19].…”
Section: Discussionmentioning
confidence: 99%